Neither Repression Nor Concession? A Regime's Attrition against Mass Protests. (October 2017) - Yuen, Samson; Cheng, Edmund W
Protest activists employ various strategies to challenge regimes, and regimes deploy multifaceted tactics to respond to such challenges. Existing studies on regime protest responses focus on repression and concession, but little attention is devoted to toleration, which is often regarded as government inaction. Drawing on primary sources and interviews, this article analyses regime responses to Hong Kong's Umbrella Movement to expand the conceptualisation of toleration. First, it demonstrates that regimes adapt multiple strategies to protesters' reactions rather than adhering to a single response. Second, it shows that toleration, other than ignoring protests, entails proactive tactics that we summarise as attrition. While 'tolerating' street occupation, the regime sought to eliminate political opportunities by maintaining elite cohesion, increase participation costs by mobilising countermovements and bolster legitimacy by leveraging the court as a revered institution. This new conceptual distinction thus captures regime innovation in counteracting protests and broadens the typology of regime responses.